KEBIJAKAN PEMERINTAH MENGENAI PENANGANAN ANAK PELAKU TINDAK PIDANA NARKOBA (STUDI KASUS DI PROVINSI DKI JAKARTA) - Oksimana Darmawan (Universitas Suryakancana, 2017)
This study is based on the number of cases of children dealing with the law concerning drug abuse. In the concept of human rights, the government including law enforcement officials are required to provide protection concerning the best interests of children, especially child rehabilitation, but on the other hand, there are a number of regulations governing the criminal misuse of narcotics. The research problem is how to arrange children of the perpetrators of criminal acts of drug abuse, and how the rehabilitation policy is given to the child of the perpetrators of the act of drug misuse. The research method used the qualitative approach to a case study. The results of the study show that the Narcotics Act implies that the child is not old enough to be positioned as a victim, since drug abuse is caused by an older person (adult), while the criminal arrangement for children is in the Criminal Justice System Act; the lack of a common perception among law enforcement officials, in relation to medical or social rehabilitation or imprisonment for children; the recommendations of an integrated assessment team (IAT) are often excluded from the investigator; corrections bureau is often excluded from making IAT. The advice given is the need to strengthen the synergy of law enforcement officers, especially related to the role of corrections bureau in the IAT.Â Keywords: Children, Drugs, Rehab, Law Enforcement, and Integrated Assessment Team (TAT).